3D OMP algorithm for 3D parameters estimation in bistatic MIMO radar. Issue 2 (23rd February 2017) - Zhang, Dong; Zhang, Yongshun; Feng, Cunqian
Abstract : A three‐dimensional (3D) signal sparse representation (SR) model that can be used for joint Doppler frequency, direction of departure and direction of arrival estimation in bistatic multiple‐input–multiple‐output radar is built. Then, a fast 3D orthogonal matching pursuit (OMP) algorithm is put forward to estimate the 3D parameters. First, the problem of targets 3D parameters joint estimation is decomposed into three estimation problems whose computation burden is decreased. Then, the high‐resolution 3D parameters of all targets are got by solving a very small‐scale SR problem. Numerical simulations verify that the proposed algorithm can get similar estimation accuracy and decrease the computational burden compared with the traditional 1D OMP algorithm.